Improving Employee Performance Through Achievement Oriented Work Motivation - Damarwulan, Liza Mumtazah; Dibyantoro, Dibyantoro (Journal Research of Social Science, Economics, and Management, 2022)
The higher the level of competition in the industrial sector, it is necessary for the company's efforts to respond well to this in order to survive through internal strategies in the form of improving employee performance. Training and competence are found to be one of the factors that can improve employee performance. The main purpose of this study is to build a model in an effort to improve employee performance involving achievement-oriented work motivation as an intervening variable the effect of training effectiveness and soft skill competence on employee performance. The population in this study are employees of companies engaged in the manufacturing sector with 276 employees. Samples were taken by 100 employees using purposive random sampling method. Structural Equation Modeling (SEM) was used to test the statistical significance of the path coefficients against the five (5) established hypotheses. The findings of the study indicate that the effectiveness of training and soft skill competencies have a positive and significant influence on achievement-oriented work motivation. Effectiveness of training, soft skill competence, and achievement-oriented work motivation have a positive and significant influence on employee performance.